Green Synthesis of Copper Nanoparticles and Evaluation of its Antioxidant and Antibacterial Efficacy - Moulana Kareem, Md.; Vijaya Lakshmi, G. (Asian Journal of Chemistry, 2022)
The current study presents a simple and green method for the optimal synthesis of copper nanoparticles (CuNPs) using Cu(CH3COO)2 and aqueous extract of Terminalic chebula fruit as a reducing and capping agent. UV-vis spectroscopy absorbance at 580 nm was used to characterize the resultant CuNPs. Further FT-IR analysis revealed that the existence of phytochemicals, which reduce Cu2+ ions to Cu and stabilize the resultant CuNPs. Transmission electron microscopy (TEM), scanning electron microscopy (SEM) and X-ray diffraction (XRD) were employed to investigate the shape and crystalline phase of CuNPs. The CuNPs were spherical in shape and averaged 23.68 nm in size. The copper nanoparticles inhibited Gram-negative E. coli more efficiently than Gram-positive S. aureus with the inhibition zones of 14.5 and 9.2 mm, respectively. Furthermore, these CuNPs exhibited dose-dependent free radical scavenging activity, with an EC50 for DPPH of 44.65 μg/mL.